2015
DOI: 10.1017/s1355770x15000248
|View full text |Cite
|
Sign up to set email alerts
|

A matter of good taste: investigating preferences for in-house water treatment in peri-urban communities in Cambodia

Abstract: Low demand for safe water may partly result from a perceived distaste towards or the inconvenience of treatment methods. This paper analyzes preferences for water quality improvements in peri-urban Phnom Penh. The authors first analyze data from a discrete choice experiment in which respondents selected their preferred alternative from generic options varying in cost, taste acceptability, effectiveness against diarrhea and quantity of water treated. The choice patterns suggest that demand for water treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For example, the underlying samples used to create BASELINE3 (representing some access to a private water connection by Observations 171 a majority of the sample) range from about 55 percent for a sample of households in Shoshong, Botswana as documented by Kadisa (2013), to full connectivity to a private water system for one in Matiguás, Nicaragua as documented by Vásquez et al (2012). 5 Moreover, these variables cannot fully capture differences in baseline quality-such as water reliability, pressure, color, or taste-that may also be important determinants of the benefits that accrue to households from enhanced access (Jeuland et al, 2015;Yang et al, 2006 …”
Section: Meta-regression Modelsmentioning
confidence: 99%
“…For example, the underlying samples used to create BASELINE3 (representing some access to a private water connection by Observations 171 a majority of the sample) range from about 55 percent for a sample of households in Shoshong, Botswana as documented by Kadisa (2013), to full connectivity to a private water system for one in Matiguás, Nicaragua as documented by Vásquez et al (2012). 5 Moreover, these variables cannot fully capture differences in baseline quality-such as water reliability, pressure, color, or taste-that may also be important determinants of the benefits that accrue to households from enhanced access (Jeuland et al, 2015;Yang et al, 2006 …”
Section: Meta-regression Modelsmentioning
confidence: 99%
“…Nearly all of these articles concern Sub‐Saharan Africa. Despite the paucity of published studies and their relatively narrow geographic focus, there is growing recognition of the importance of multiple household water sources and a growing body of literature acknowledges the practice around the world and/or calls for further research (Ahmed & Hossain, ; Brown et al, ; Dos Santos et al, ; Evans et al, ; Foster & Hope, ; Henry, ; Jeuland et al, ; MacDonald et al, ; Overbo et al, ; Shaheed et al, ; Thompson et al, ; Wang et al, ). This dispersed literature lacks consistent vocabulary and methodologies; published studies can be difficult to find; and most articles cite few or no prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…has a disgusting taste of chemicals, are more willing to pay. To this respect, Jeuland et al (2015) found a positive WTP for treated water, thus emphasizing the importance that individuals give to those water attributes, as taste or smell, that are experienced directly in comparison with other ones that should be inferred such as health benefits.…”
Section: Resultsmentioning
confidence: 99%